1976
DOI: 10.1007/bf01071952
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of mucopolysaccharide in the pancreatic juice in chronic pancreatitis

Abstract: In order to study whether or not mucosubstance increases occur in the pancreatic juice of patients with chronic pancreatitis, hexosamine was measured in duodenal aspirates during the secretin phase (S-40) following pancreozymin-secretin stimulation in 16 normal subjects, 37 patients with chronic pancreatitis, 6 patients with alcoholism, 13 patients with gallstones, and 11 patients with peptic ulcer. The hexosamine concentrations in the pancreatic secretions showed a negative correlation with the bicarbonate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…These results suggest that PDH enhanced nonenzymatic proteins secretion, and such proteins were attributable to an increase in the protein concentration in PJ. Because nonenzymatic proteins have been shown to relate with the viscosity of PJ or formation of protein plugs (22,23,51), it is likely therefore that these proteins play some roles in the progression of pancreatic fibrosis in our model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results suggest that PDH enhanced nonenzymatic proteins secretion, and such proteins were attributable to an increase in the protein concentration in PJ. Because nonenzymatic proteins have been shown to relate with the viscosity of PJ or formation of protein plugs (22,23,51), it is likely therefore that these proteins play some roles in the progression of pancreatic fibrosis in our model.…”
Section: Discussionmentioning
confidence: 98%
“…Sarles et al (39) previously reported that protein plugs are present in all small pancreatic ducts in the initial lesions of human CP. In addition, several studies have shown that the viscosity of pancreatic juice (PJ) is increased in patients with CP (22,51). Moreover, Bradley (6) demonstrated a significantly higher pancreatic ductal pressure in patients with CP compared with that in control subjects.…”
mentioning
confidence: 98%
“…Elevated pancreatic duct pressure has been demonstrated in patients with chronic pancreatitis 40 , which may be due to increased viscosity of pancreatic juice 41 , 42 . However, it was unclear whether chronic pancreatitis arises from or leads to increased pancreatic duct pressure until it was demonstrated experimentally that sustained elevation of pancreatic duct pressure in rats caused chronic pancreatitis 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of alcoholic chronic pancreatitis, continuous drinking by the patient is considered to increase the protein concentration of the pancreatic juice (7,8) and thus its viscosity (9, 10), leading to formation of a protein plug in the pancreatic duct (11,12) and recurrent attacks of pancreatitis. Attempts have been made to treat such patients with secretin (13), and endoscopic removal of the pancreatic juice and protein plug (14), but it is difficult to achieve a permanent effect.…”
Section: Discussionmentioning
confidence: 99%